DESIGN THINKING DALAM PENGEMBANGAN UI/UX MODUL PENILAIAN REKRUTMEN: STUDI KASUS SELEKSI DOKUMEN DAN WAWANCARA - Kurniati Asmar; Andi Indra Saputra Alamsyah; Risnawati; Maududi Lamparawi Magenda; Tri Wahyu Septyani (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
The evaluation stage of the recruitment process is often hindered by impracticality due to the fragmentation of applicant documents and assessment instruments, which diminishes the cognitive focus and accuracy of evaluators. This study aims to design an integrated digital recruitment system prototype using the Design Thinking approach. During the empathize and define stages, the primary issues identified were procedural complexity and unstructured interview workflows. Solutions were developed through the ideate and prototype stages, resulting in an internal platform that unifies digital document verification with an interview assessment module. The system's key features include a side-by-side interface that integrates standardized interview guides with electronic assessment forms, along with automated score accumulation and ranking features. The testing phase involved four expert respondents using the System Usability Scale (SUS) instrument, yielding an average score of 74.37 (Good/Acceptable category). The results demonstrate that the integration of features into a single platform effectively minimizes administrative barriers and enhances the objectivity of final decision-making. This research contributes to optimizing recruitment operational efficiency through the automation of candidate data processing